Recreational activity of students from Preschool Teacher Training College in Sabac - Pantić Zoran S.; Stamatović Milovan V. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2018)
This article deals with free time and recreation of college students. The aim of this research is to establish how much free time students from Preschool Teacher Training College in Sabac have and how they use it, as well as how much they are engaged in sports and recreational activities. The sample consisted of 60 female students aged 22 (±6 months). A survey with 15 questions was used. Chi-squared test was applied in statistical analysis. Results showed that only 30% of respodents had enough free time and 83,3% of them had additional needs for motion. The majority of them, 70% would choose walking and spending time in countryside. Half of them is physically active 1-2 times a week. 30% regulary go to the concerts, and majority, 71,7% sometimes go to the cinema. 55% regulary pay home visits, and 53,3% sometimes go to the cafes and discos. 56,7% sometimes play cards and 20% play on regular basis. One quarter of them never do any physical activities in their free time. 63,3% go for a walk 3-4 times a week. 66,7% sometimes go on a picnic. The majority feel capable or partially capable of making their own programme of exercising. 58,3% gained necessary knowledge of doing exercises in free time. 35% would test their mobility skills. 41,7% have partial knowledge of the importance of physical exercise on health and human body. A lack of free time, lifestyle, poor organized free time have direct impact on physical engagement of female students. A large scale of education about the importance of physical activities is necessary, as well as about testing and monitoring of health condition.